2019
DOI: 10.1111/jne.12797
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perioperative stress on central and peripheral oxytocin and arginine‐vasopressin concentrations

Abstract: Perioperative stress provides not only physical, but also psychic and emotional aspects, which may influence the hypothalamic neuropeptide system. Studies investigating the perioperative course of central neuropeptide activity are missing. Therefore, the present study aimed to determine perioperative fluctuations in central and concomitant peripheral concentrations of the hypothalamic neuropeptides oxytocin (OXT) and arginine‐vasopressin (AVP), as well as their impact on perioperative anxiety and depression. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This might be indicating a role for central MCN projections to other brain regions or dendritic release in inducing early anaesthetic effects. Indeed, anaesthesia itself does seem to affect circulating AVP levels [33][34][35], although increases do occur during intense surgical stimulation [36]. Interestingly, both the CC and SON displayed phosphoproteomic adaptations to GA, suggesting that Fos expression is not a defining marker for cellular change following GA. How are phosphorylation responses to GA influencing neuronal activity or function?…”
Section: Discussionmentioning
confidence: 99%
“…This might be indicating a role for central MCN projections to other brain regions or dendritic release in inducing early anaesthetic effects. Indeed, anaesthesia itself does seem to affect circulating AVP levels [33][34][35], although increases do occur during intense surgical stimulation [36]. Interestingly, both the CC and SON displayed phosphoproteomic adaptations to GA, suggesting that Fos expression is not a defining marker for cellular change following GA. How are phosphorylation responses to GA influencing neuronal activity or function?…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is the time of sample collection, which is assumed to influence hypothalamic neuropeptide concentrations especially in the central compartment [ 22 ]. However, studies on neurocritical care patients which mainly examined patients with aneurysmal subarachnoid hemorrhage, showed that AVP secretion neither in the blood nor in the CSF follows a diurnal rhythm [ 23 , 24 ]. In our study on a more heterogenous patient collective, samples were obtained only during day shifts, where a steady level of light and noise prevailed at the ward to minimize potential external influences on AVP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…According to one study [22], dogs with a history of aggression had lower free AVP but higher total plasma AVP than matched controls. Furthermore, a recent human study done in patients with perioperative anxiety, demonstrated that there is a weak correlation between AVP concentrations in saliva, blood, and cerebrospinal fluid (CSF), which casts some doubt on the role of salivary, or blood, AVP levels as a representation of central AVP activity [43].…”
Section: Discussionmentioning
confidence: 99%